2018
DOI: 10.1002/1873-3468.13301
|View full text |Cite
|
Sign up to set email alerts
|

Dual conformation of the ligand induces the partial agonistic activity of retinoid X receptor α (RXRα)

Abstract: 1‐[(3,5,5,8,8‐pentamethyl‐5,6,7,8‐tetrahydronaphthalen‐2‐yl)amino]benzotriazole‐5‐carboxylic acid (CBt‐PMN), a partial agonist of retinoid X receptor (RXR), has attracted attention due to its potential to treat type 2 diabetes and central nervous system diseases with reduced adverse effects of existing full agonists. Herein, we report the crystal structure of CBt‐PMN‐bound ligand‐binding domain of human RXRα (hRXRα) and its biochemical characterization. Interestingly, the structure is a tetramer in nature, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…When hRXRα-LBD/ 14 and the apo-form in PDB ID 1G1U were merged (Figure S8A, Movie S1), it could be seen that their conformations are almost the same. It is reported that the RXR partial agonist 13 induces two different conformations of hRXRα-LBD, that is, activated and inactivated . The inactivated conformation (PDB ID: 5ZQU, chain B) resembles hRXRα-LBD/ 14 (Figure S8B).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When hRXRα-LBD/ 14 and the apo-form in PDB ID 1G1U were merged (Figure S8A, Movie S1), it could be seen that their conformations are almost the same. It is reported that the RXR partial agonist 13 induces two different conformations of hRXRα-LBD, that is, activated and inactivated . The inactivated conformation (PDB ID: 5ZQU, chain B) resembles hRXRα-LBD/ 14 (Figure S8B).…”
Section: Resultsmentioning
confidence: 96%
“…It is reported that the RXR partial agonist 13 induces two different conformations of hRXRα-LBD, that is, activated and inactivated. 46 The inactivated conformation (PDB ID: 5ZQU, chain B) resembles hRXRα-LBD/14 (Figure S8B). The root-mean-square deviation for Cα atoms, which is a measure of the homology of the structure, was 0.258 Å for hRXRα-LBD/14 and PBD ID 1G1U and 0.334 Å for hRXRα-LBD/14 and hRXRα-LBD/13, suggesting that the RXR conformation in hRXRα-LBD/14 is similar to that of the apo-form.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To investigate the molecular basis of the interaction of compounds 2 and 12 with RXRα, molecular docking analysis of 9cRA, 2 , and 12 with RXRα-LBD (Protein Data Bank ID: 1G1U, 1FM6, and 5ZQU ) was performed (Figure C–E). The major structural difference between RXRα-LBD and other PPAR-LBDs is found in H12.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the trifluoromethyl group of 1 is not involved in the interaction with RXRα-LBD, supporting the idea that it may instead play a role in suppressing free rotation at the bond between the hydrophobic moiety and the acidic pharmacophore. We also reported a structurally flexible RXR partial agonist CBt-PMN ( 5 , Figure B), which contains a benzotriazole skeleton, binds to RXR, and induces conformational changes of RXR into active and inactive forms . We hypothesized that replacing the benzimidazole of 1 with a benzotriazole moiety would yield a compound that would bind to the orthosteric site and also other site(s) and that its antagonistic activity would be decreased as a result of decreased specificity for the LBP, even though its K d toward RXR would be maintained.…”
mentioning
confidence: 99%